97 A Novel Approach to Teaching Anatomic Pathology Subspecialties to Medical Students: Dual-Headed Microscope Sessions. (11th January 2018) - Chen, Tiffany; Garcia, Joaquin
Abstract: Introduction: Medical students spend limited time learning about the practice of pathology and laboratory medicine. Medical schools struggle with finding efficacious approaches to teaching pathology and its subspecialties to medical students. This pilot study utilized a dual-headed microscope, and incorporated blended and self-directed learning approaches to teach a complex pathology subspecialty to a medical student. Methods: A third-year medical student and head and neck pathologist reviewed 800 salivary gland consultation cases over a 10-hour span in tandem using dual-headed microscope sessions. A 10-minute introduction (didactic lecture) on salivary gland pathology was given prior to microscope session. Between the first and last five hours of dual-headed microscope sessions, the student conducted five hours of self-directed learning. The learning team focused dialogues on terminology (ie, biphasic), differential diagnostic categories (ie, oncocytic), ancillary laboratory testing (ie, androgen receptor), and treatment algorithms (ie, radiation). Results: Terminology, differential diagnostic categories, ancillary laboratory testing, and treatment algorithms were elucidated by the pathologist and reiterated incessantly by the medical student. Significant improvement in salivary gland pathology terminology, diagnostic acumen, ancillary laboratory test selection, and treatment forecast was observed by the pathologist. The student demonstrated senior resident-level proficiency in salivary gland pathology on written examination at the completion of the pilot study. Conclusion: The dual-headed microscope remains a cornerstone of education in anatomic pathology, reinforcing the apprenticeship model between student and teacher. This instrument creates an ideal learning platform for medical students as it fosters enthusiasm and facilitates repetitive cognition, as well as challenges students to create their own diagnostic algorithms and hone their problem-solving abilities.